Use of a local computer network in the process of teaching Mathematics at school - L. G. Zvereva; K. A. Khalatyan; E. M. Petlina (Вестник Майкопского государственного технологического университета)
At present in the context of modernization of the educational system, a modern teacher cannot succeed without knowledge of the possibilities of information and communication technologies (ICT). As the works of domestic researchers show [1; 3; 5], these technologies in Mathematics lessons can significantly increase the effectiveness of teaching. However, in the education system, the experience of using a private component of ICT – local computer networks (LCN) is not as long as, for example, in enterprises [9]. On the basis of the foregoing, the research problem is to form methodology for the use of LCN in the process of teaching Mathematics.The purpose of the research is to reveal the possibilities of using the LCN in the process of teaching Mathematics at school. To achieve this goal, the works devoted to the problems of using information technologies in teaching Mathematics have been analyzed, and a stating experiment in MBOU Lyceum No. 35 in Stavropol have been conducted to identify the possibilities of using LCN. In the course of the research the methods of analysis, synthesis and systematization of material on the problem of the use of LCN in education, questionnaires and conversations with teachers have been used.On the basis of literature analysis and the conducted ascertaining experiment, the authors have classified the LCN tools according to their methodological purpose, and have given the possibilities and requirements for the use of a local network in teaching Mathematics at the levels of basic and secondary general education. Along with this, the article reveals the demand for the use of LCNs at the levels of basic and secondary general education.